THU0554 COMORBIDITY AND HEALTH CARE UTILIZATION IN PERSONS WITH SJÖGREN'S SYNDROME: A CLAIMS DATA ANALYSIS. (13th June 2020) - Albrecht, K.; Dörner, T.; Redeker, I.; Karberg, K.; Marschall, U.; Zink, A.; Callhoff, J.
Abstract : Background: Sjögren's syndrome (SS) can affect numerous organs, including the muscles, the peripheral nervous system, kidneys and lungs. Epidemiological studies assessing comorbidity and health care utilization are needed to improve health care for this multifaceted disease. Objectives: To capture comorbidity and medication of persons with SS in a population-based cohort in comparison to matched controls. Methods: Individuals with an outpatient diagnosis of M35.0 (ICD-10) in ≥2 quarters of a year or an inpatient diagnosis of M35.0 were identified in a German statutory health insurance fund covering 7.2 million people. Persons in rheumatologic care were grouped by incident or prevalent diagnosis and by co-existing autoimmune disease (sSS) or primary (p)SS and compared to age- and sex-matched controls regarding comorbidity (ICD-10), medical prescriptions, hospitalization and inability to work in the previous year. Results: In 2018, 7, 374 persons (0.1%) had incident and 53, 917 persons (0.73%) prevalent SS diagnosis, and 5, 920 (11%) were in rheumatologic care. Of these (90% female, mean age 66 years), 3, 431 (58%) had further autoimmune disease (sSS), mostly rheumatoid arthritis (80%) and systemic lupus erythematosus (13%). Compared to controls, frequent comorbid conditions in SS were hypertension, osteoarthritis, osteoporosis and depression (table 1 ). Systemic antirheumatic drugs were prescribed in 31% (pSS) and 66% (sSS) while < 4% received topical therapies. Glucocorticoids (7% controls/34% pSS/59% sSS), NSAIDs (28%/41%/45%), opioids (9%/15%/22%), analgesics (19%/30%/36%) and antidepressants (14%/21%/22%) were more frequently prescribed in SS than in controls, and also hospitalization (21%/32%/39%) and inability to work in persons <65 years (41%/48%/44%, median days 17/24/31) were more frequent in pSS and sSS than in controls. Conclusion: SS claims diagnosis is associated with substantial comorbidity and frequent prescription of anti-inflammatory drugs, analgesics and antidepressants. The individual and societal burden of SS shows that, in addition to effective treatment strategies, intensive attention to comorbidities is important in this disease. Acknowledgments: Funding The study was supported by the Wolfgang Schulze Foundation of the German Rheuma-Liga Disclosure of Interests: Katinka Albrecht: None declared, Thomas Dörner Grant/research support from: Janssen, Novartis, Roche, UCB, Consultant of: Abbvie, Celgene, Eli Lilly, Roche, Janssen, EMD, Speakers bureau: Eli Lilly, Roche, Samsung, Janssen, Imke Redeker: None declared, Kirsten Karberg: None declared, Ursula Marschall: None declared, Angela Zink Speakers bureau: AbbVie, Amgen, BMS, Gilead, Hexal, Janssen, Lilly, MSD, Pfizer, Roche, Sanofi Aventis, UCB, Johanna Callhoff: None declared